2018
DOI: 10.1155/2018/6413179
|View full text |Cite|
|
Sign up to set email alerts
|

Surfaces and Air Bacteriology of Selected Wards at a Referral Hospital, Northwest Ethiopia: A Cross-Sectional Study

Abstract: Background The hospital environment is a source of medically important pathogens that are mostly multidrug resistant (MDR) and posing a major therapeutic challenge. The aim of this study was to assess the surface and air bacteriology of selected wards at Felege Hiwot Referral Hospital (FHRH), Northwest Ethiopia. Methods A cross-sectional study was carried out from 15th February to 30th April 2017. A total of 356 surface and air samples were collected from selected wards using 5% sheep blood agar (Oxoid, UK) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 19 publications
7
27
5
Order By: Relevance
“…The results of our study showed substantial contamination of inanimate environments by varied groups of bacteria, including both Gram-positive (56.3%) and Gram-negative (43.7%). Similar reports were documented by several authors from other studies in Ethiopia and abroad such as Gondar, Ethiopia (60.5% vs 39.5%), 37 Northwest, Ethiopia (81.6% vs 18.4%), 16 Iran (60.7% vs 39.3%) 38 and Nigeria (52.2% vs 47.8%). 39 The dominance of GPB could be explained by the fact that these bacteria, being devoid of the lipid-dominant desiccation-prone outer membrane, have a natural ability to retain their viability on abiotic hospital environments for several days to months.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of our study showed substantial contamination of inanimate environments by varied groups of bacteria, including both Gram-positive (56.3%) and Gram-negative (43.7%). Similar reports were documented by several authors from other studies in Ethiopia and abroad such as Gondar, Ethiopia (60.5% vs 39.5%), 37 Northwest, Ethiopia (81.6% vs 18.4%), 16 Iran (60.7% vs 39.3%) 38 and Nigeria (52.2% vs 47.8%). 39 The dominance of GPB could be explained by the fact that these bacteria, being devoid of the lipid-dominant desiccation-prone outer membrane, have a natural ability to retain their viability on abiotic hospital environments for several days to months.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, out of 164 environmental samples from swabs, 141 (86%) were positive for bacterial contamination which has similarly been reported from studies like Zimbabwe (86.2%) 14 and Morocco (96.3%). 28 In contrast to our result, studies conducted from Gaza Strip (24.7%), 29 Sudan (29.7%), 30 Uganda (44.2%), 31 Nigeria (39.4%), 32 and Bahir Dar, Northwest Ethiopia (39.6%) 16 reported far lower surface contamination rates. Differences in hand hygiene, ventilation system, sterilization, and disinfection techniques could account for these discrepancies.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Recovery of microbial pathogens from fomites supports the earlier reports of isolating similar microbes from toilet door handles in various settings including; hospitals in India (Lincy et al, 2016), beds and door handles in Kiwoko Hospital in Uganda (Segujja et al, 2016) and hospital surface samples in Ethiopia (Getachew et al, 2018). Recovery of methicillin-resistant S. aureus from different surfaces including; glass, vinyl floor tile, countertop and stethoscopes have been documented by Williams and Davis, (2009).…”
Section: Discussionsupporting
confidence: 75%